Successful Use of Interferon-Gamma for Refractory Disseminated Candida Tropicalis Infection in a Pediatric Patient with Acute Myeloid Leukemia and Heterozygous CARD9 Mutation - Kleinschmidt, Katharina; Troeger, Anja; Foell, Juergen; Jakob, Marcus; Corbacioglu, Selim (Archives of Clinical and Medical Case Reports, 2022)
Invasive fungal infections remain among the most frequent severe and fatal complications of oncology, despite effective antifungal agents. Genetic aberrations may additionally increase the individual patient’s susceptibility to invasive mycosis, with the need for an intensified treatment, such as adjunctive immunotherapy combined with standard antifungal medication. Interferon-gamma (IFN-γ) as an immunostimulatory agent may represent a promising surrogate to reactivate the cytotoxic activity of macrophages in patients with ‘blind spots’. We report the case of a pediatric patient with AML and disseminated candida tropicalis infection, bearing a heterozygous CARD9 mutation, who was treated successfully with combined IFN-γ and conventional antifungal therapy.